The Evaluation of Nanoemulsion Cinnamon Extract (Cinnamomum burmanii) on Lipcream as Natural Dyes - Agustin, Eriska; Agustina, Maulia (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
The use of nanoemulsion in the cosmetic field has been widely developed, one of which is the use of natural dyes from natural ingredients. Nanoemulsion has the ability to provide a wider variety of colors due to its high solubilization and translucent nature. The effort to produce natural dyes can be obtained form natural resources, one of which is the cinnamon plant. Beside having a distinctive aroma, cinnamon can also produce a brownish pigment that comes form the cinnamaldehyde compound. In this study, Cinnamon extract samples were obtained by maceration method using ethanol solvent pa, cinnamon extract nanoemulsion preparations were made using a sonicator bath for 60 minutes, and lipcream preparations were made using the trituration method. The results showed that the cinnamon extract from formula F1 nanoemulsion had a particle size of 273±0.032 nm. Evaluation of the lipcream preparations carried out included organoleptics which produced a distinctive aroma of cinnamon, the resulting color was softer brown compared to conventional lipcream preparations, the texture was soft and homogeneous, the resulting pH test met the pH requirements of the lip cream, namely 4.93-5.02, adhesion 5-6 cm and 4-5 seconds of adhesion (p>0.05). The cinnamon extract nanoemulsion preparations produced particle sizes that entered the nano range and lipcream preparations produced color pigments that were softer than conventional preparations.